My Exposure to Violence: translation and cultural adaptation to the BR Portuguese - Marcos Clint Leal de Carvalho; Raimunda Hermelinda Maia Macena (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To translate and adapt the My Exposure to Violence instrument for measuring exposure to community violence into Brazilian Portuguese. METHODS Psychometric study of translation and cross-cultural adaptation in seven stages: (I) initial translations, (II) synthesis of translations, (III) back-translations, (IV) cross-cultural pre-adaptation, (V) evaluation by committee of judges, (VI) pre-test, and (VII) submission to the original author. In step V eight judges evaluated the instrument's equivalence of content, and the content validity index was calculated for each item (CVI-I) and for the average of the instrument (CVI-M), considering a CVI-I ≥ 0.78 as excellent and a CVI-M ≥ 0.80 as acceptable and ≥ 0.90 as excellent. The pre-test was conducted with 39 adolescents enrolled in an educational institution in Fortaleza, state of Ceará. The understandability of the items was evaluated. RESULTS In step I, two translations were produced with few differences between them. These were resolved in step II, by generating the synthesis version (T12). In step III, the back-translated items reflected the same content as the items in the original version. In step IV, T12 was revised by the authors, who made specific linguistic changes in order to facilitate understanding. In step V, one item (22) presented CVI < 0.78. Due to the relevance of the suggestions, 19 of the 23 items (82.60%) were modified. The CVI-M of the instrument was 0.92. In stage VI, the mean age of the participants was 17.48 years (SD = 1.27). The pre-final version had 21 out of 23 items (91.30%) fully understood by more than 90% of the participants. No changes were made to the final version. CONCLUSIONS My Exposure to Violence was cross-culturally adapted into Brazilian Portuguese, and was well understood by the target population. Other psychometric properties, such as reliability and validity, should be evaluated in further studies to strengthen the evidence of the translated and adapted version.